MODELAGEM MATEMÁTICA COMO METODOLOGIA PARA O DESENVOLVIMENTO DO LETRAMENTO ESTATÍSTICO NO ENSINO MÉDIO - Loli, Adriana Cristina (2021)
This study aimed to investigate how Mathematical Modeling, as a teaching methodology, contributed to the development of Gal's Statistical Literacy in 3rd grade high school students. In this sense, the present work involved a teaching experience with 51 students of a public school in the city of Guarapuava - PR. Throughout three months, during mathematics classes, the process of Mathematical Modeling happened, according to Burak (1992), experiencing all its stages, from the choice of theme and elaboration of the research question up to the analysis, divulgation and review of the results. The research was qualitative, approaching the students' productions in their natural environment, the classroom. The analysis of the data, instead, was done according to the deducted categories defined by Gal (2002), which are related to statistical knowledge, mathematical knowledge, contextual knowledge, critical questioning and dispositional elements.It was observed that Mathematical Modeling is a great motivator to the students, being a methodology that favored interdisciplinarity, critical thinking, student protagonism and the understanding that the purpose of Statistics is decision making and knowledge of reality. From the activities experienced, it was elaborated, as an educational product associated with this work, a guide with scripts of activities, containing all the commented steps for its application. It is hoped that this research and the formulated educational product can contribute to the Elementary School teachers who wish to insert Mathematical Modeling in their Statistics classes.